Smart manufacturing paradigms in the context of industry 4.0: Bibliometric analysis - El Assad Nouhaila; Dachry Abdelmounaime; Fouraiji Hicham; Dachry Wafaa; Messaoudi Najat (E3S Web of Conferences)
Following each industrial revolution, spanning from Industry 1.0 to Industry 4.0, a distinct manufacturing paradigm has consistently emerged. In the current manufacturing environment and consumer-driven markets, Mass Customization and Mass Personalization are the newer smart manufacturing paradigms. Those novel approaches are designed to offer customers personalized products and services, all while preserving the efficiency of Mass Production. Within this framework, a bibliometric analysis was conducted in order to review and analyse the existing literature. The main findings reveal numerous parallels and differences between Mass Customization and Mass Personalization, especially in aspects such as scope, customer involvement, product variety and flexibility. Simultaneously, there are various limitations revolving around data availability and product uncertainty. Those smart manufacturing paradigms are studied within the context of Industry 4.0, and thus our study also focus on the impact and challenges of this fourth industrial revolution on Mass Customization and Mass Personalization.